Atributos físicos e mecânicos de um latossolo conduzido sob diferentes sistemas de manejo - Dapper, Felipe Puff (2020)
The soil quality physical has great importance in the development of roots of the plants, therefore areas under no-tillage can present compaction problems result loss to crops grown in these areas. Machine traffic is the main causative agent of soil compaction, considering that during the cycle of a culture the same area needs to be trafficked several times in order to be able to carry out cultural treatments. Thus the pressures exerted by the weight of the machines cause deformations in the soil structure, expelling air from the pores causing densification the main factors that is related to the deformation of the structure is the water content in soil matrix, the higher the moisture content of the soil the greater its susceptibility to compaction. Compacted soils offer resistance to root development which can result in a small volume of explored soil impairing nutrient absorption. The objective of this work was to correlate the physical attributes of the soil, to estimate of loud bearing capacity and to estimate last limiting water range (IHO) in different managements conducted under no-tillage. The hypothesis tested in this work was that the time of direct planting without mechanical intervention favors the structuring of the soil ensuring that the soil is more resistant to the agents the cause compaction. Five areas were evaluated namely: No-till for twenty years (SPD 20) no- for ten years (SPD 10), no-till for three years (SPD 3), chisel cultivation (Esc) and native forest (Mata). Soil samples were collected in three layers (0- 5; 10-15; 25-30 cm), the physical attributes were measured in the laboratory, so the models of load bearing capacity in the last limiting water range. The physical attributes of the soil change with the increase in the time of no-tillage execution in ensuring that the soil is able to support aggregates load. For values of 3 and 3,5 MPa, the SPD 20 had and IHO greater than zero, showing that the SPD 20 has good conditions for root development.